Strategi Manajemen Diversitas Dalam Meningkatkan Kinerja Tim - Lusi Emilia Wulandari; Devi Noviana (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explore diversity management strategies in improving team performance in the context of human resource management (HR). Using a literature study method, this research analyzes various strategies used by organizations to manage diversity and inclusion, as well as their impact on team creativity and performance. The research results show that well-managed diversity can improve team performance through positive synergy and higher innovation. In addition, these findings also highlight the importance of inclusion policies that support the participation of all team members.